Menstrual Cycle Patterns in Final Year Student, Faculty of Medicine, Universitas Sriwijaya - Septi Purnamasari; Bagus Eko Prasetya; Adnan Abadi; Heriyadi Manan; Raissa Nurwany (HM Publisher, 2023)
Normal menstrual cycles occur every 25-30 days, with the length of menstruation with an average cycle duration of 28 days. If the menstrual cycle is less than 21 days or more than 35 days, it is considered a cycle of irregular menstruation. Irregular menstruation is caused by changes in female hormone levels associated with health behavior, obesity, stress, and physical activity. This study aimed to describe the pattern of the menstrual cycle in final-year female students of the Faculty of Medicine, Universitas Sriwijaya. The research design used a cross-sectional study with a total study population of 144 people. Data were obtained from questionnaires filled out by students via the Google form and then analyzed using the chi-square test. The results of the study showed that most students experienced normal menstrual cycles, as much as 62.1%. The most common menstrual disorder experienced by female students was dysmenorrhea, as much as 61.3%. Based on the chi-square test, it was found that there was no relationship between physical activity and the menstrual cycle (p=0.648). In conclusion, there is no relationship between physical activity and the menstrual cycle.